The Influence of Education Costs, Location, and School Image on Parents’ Decisions to Choose Educational Services at SDIT Al Madinah Pontianak - Fitri Nadia Ulandari; Neni Triana M (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of education cost, location, and school image on parents’ decisions to choose the educational services of SDIT Al Madinah in Pontianak City. This study uses an associative approach to identify the relationships and effects among the variables examined. The population in this study comprises all parents of students at SDIT Al Madinah Pontianak, with a sample of 100 respondents determined through probability sampling techniques. The research instruments were tested through validity and reliability tests to ensure the feasibility of the measuring tool. Furthermore, the classical assumption tests used include the normality test, linearity test, and multicollinearity test. Hypothesis testing was conducted using multiple linear regression analysis, correlation coefficient, coefficient of determination, simultaneous test (F test), and partial test (t test). The results of the multiple linear regression analysis produced the regression equation: Y = 1.183 + 0.281X₁ + 0.163X₂ + 0.305X₃. The correlation coefficient value of 0.777 indicates a strong relationship between education cost, location, and school image with parents’ decisions. Meanwhile, the coefficient of determination value of 0.604 indicates that parents’ decisions are influenced by the three variables by 60.4%, while the remaining 39.6% is influenced by other factors outside the variables examined. The simultaneous test results show that education cost, location, and school image jointly have a positive and significant effect on parents’ decisions. In addition, the partial test results also prove that each variable—education cost, location, and school image—has a positive and significant effect on parents’ decisions.